2019
DOI: 10.1515/lingvan-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for forgetfulness in dementia interaction

Abstract: The article identifies and describes conversational practices used by persons with dementia and their interlocutors to account for the former’s lack of knowledge in cases where information about their personal experiences is made relevant and expectable at a specific point in a conversation. First, they may seek to normalize the lack of knowledge by claiming that it would be difficult for anyone to know or remember the information in question. Second, they may exceptionalize it by claiming that their cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…These accounts rationalize the process of arriving at an incorrect answer, thereby normalizing it rather than imputing it to the memory problems associated with dementia (see also Lindholm, 2015). As such, they resemble the type of accounts that have been described to occur when a PWD is unable to answer a question about personal experiences (Svennevig and Landmark, 2019). Our study also revealed that in response to the repair initiations, the PWDs managed to preserve some epistemic rights, either by confirming the correction (Kristiansen et al, 2017; Mikesell, 2010), by integrating it into their own account (Black, 2011), or by opposing the correction and maintaining their original claim.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These accounts rationalize the process of arriving at an incorrect answer, thereby normalizing it rather than imputing it to the memory problems associated with dementia (see also Lindholm, 2015). As such, they resemble the type of accounts that have been described to occur when a PWD is unable to answer a question about personal experiences (Svennevig and Landmark, 2019). Our study also revealed that in response to the repair initiations, the PWDs managed to preserve some epistemic rights, either by confirming the correction (Kristiansen et al, 2017; Mikesell, 2010), by integrating it into their own account (Black, 2011), or by opposing the correction and maintaining their original claim.…”
Section: Discussionmentioning
confidence: 66%
“…The social sensitivity of not knowing has also been explored. Svennevig and Landmark (2019) found that PWDs and their interlocutors oriented to not remembering personal experiences as accountable when asked factual questions by their interlocutor. In their study, the PWDs, or their interlocutors, regularly provided accounts that either normalized the lack of knowledge, or, on the contrary, ‘exceptionalized’ it by attributing it to the dementia disease.…”
Section: Introductionmentioning
confidence: 94%
“…This utterance seems to initiate a metacommunicative parenthesis, expressing her frustration with not being able to continue the utterance, at least this is how it is interpreted by P in her understanding check (line 15). In addition, it provides an account for her inability to provide an answer, treating the problem as exceptional (Svennevig & Landmark 2019). The code-switching thus has a discourse-related function, in marking parts of the talk as being distinct from and inserted into the main activity of the talk.…”
Section: Excerptmentioning
confidence: 99%
“…Yet again, Mathias' contribution of providing an account here can be seen as a way of contributing to and ratifying his wife's selfpraise in regard to managing her chores despite occasional shortcomings. Mathias' detailed account provides evidence for a justification for Kari's forgetfulness, which Svennevig and Landmark (2019) also found in regard to forgetfulness during interaction. Overall, the practice of normalising and justifying trouble is responded to by Kari with self-praise, and it opens a possibility for a strengthened positive framing of her abilities.…”
Section: Justifying Troublementioning
confidence: 74%
“…The downplay by Mathias justifies Kari's troubles with baking since when presenting it as a rarity (i.e. Svennevig & Landmark, 2019). Kari affiliates with Mathias by responding that she does not bake much since she finds it boring.…”
Section: Mitigating Troublementioning
confidence: 99%